(untitled) (PANGEEA, 2025)
Photography plays a key role in geographical studies but also in teaching geography. For geographical photography there are some important aspects regarding the photographic technique: setting the correct size of the image, white balance, ISO sensitivity, image format, time exposure, aperture, knowing the functioning of the incorporated light bulb, focalization, the optic and digital zoom, measuring the luminosity in the scene that is about to be photographed. In this study, there will be presented the most important types of photography that are used in geography, while in the last part of the study, the most important rules that must be respected when framing and shooting are described. In the end it is presented a glossary which includes 29 terms of speciality that are used in this paper.